Changes in cognitive function after thoracoscopic and catheter ablation for atrial fibrillation. Issue 1 (10th December 2022) - Herman, Dalibor; Javůrková, Alena; Raudenská, Jaroslava; Budera, Petr; Rizov, Vitalii; Kačer, Petr; Peisker, Tomáš; Malý, Marek; Osmančík, Pavel
Abstract: Background: Comparative data regarding the effect of percutaneous and thoracoscopic ablation of atrial fibrillation (AF) on cognitive function are very limited. The aim of the study was to determine and compare the effect of both types of ablations on patient cognitive functions in the mid‐term. Methods: Patients with AF indicated for ablation procedure were included. Forty‐six patients underwent thoracoscopic, off‐pump ablation using the COBRA Fusion radiofrequency system, followed by a catheter ablation three months afterward (Hybrid group). A comparative cohort of 53 AF patients underwent pulmonary vein isolation only (PVI group). Neuropsychological examinations were done before and nine months after the surgical or catheter ablation procedure. Neuropsychological testing comprised 13 subtests of seven domains, and the results were expressed as post‐operative cognitive dysfunction (POCD) nine months after the procedure. Results: Patients in both groups were similar with respect to the baseline clinical characteristics; only non‐paroxysmal AF was more common in the hybrid group (98% vs. 34%). Major POCD was present in eight (17.4%) of hybrid patients versus three (5.7%) of PVI patients ( p  = 0.11), combined (major/minor) worsened cognitive decline was present in 10 (21.7%) hybrid patients versus three (5.6%) PVI patients ( p  = 0.034). On the other hand, combined (major/minor) improvement was present in 15 (32.6%) hybrid patients versus nine (16.9%) patients in the PVI group ( p  = 0.099). Conclusion: Hybrid ablation, a combination of thoracoscopic and percutaneous ablation, is associated with a higher risk of cognitive decline compared to sole percutaneous ablation.